Protective Effect of Rosamultin against H2O2-Induced Oxidative Stress and Apoptosis in H9c2 Cardiomyocytes. (16th July 2018) - Zhang, Ling; Liu, Yang; Li, Jian Yu; Li, Ling Zhi; Zhang, Yong Liang; Gong, Hai Ying; Cui, Ying
Abstract : Rosamultin is one of the main active compounds isolated from Potentilla anserina L., which belongs to a triterpene compound. Few studies have examined the effect of rosamultin on oxidative stress and its molecular mechanism. The aim of this present study was to elucidate the protective effect of rosamultin on H2 O2 -induced oxidative damage and apoptosis in H9c2 cardiomyocytes and its mechanism. The results showed that the pretreatment of rosamultin not only increased cell viability but also reduced the release of LDH and CK. Rosamultin inhibited a H2 O2 -induced decrease in SOD, CAT, and GSH-Px activities and an increase in MDA content. Meanwhile, ROS level, intracellular (Ca 2+ ) fluorescence intensity, and apoptosis rate in the rosamultin pretreated group were markedly decreased compared with the model group. Rosamultin pretreatment significantly reversed the morphological changes and attenuated H2 O2 -induced apoptosis. Western blot analysis showed that rosamultin enhanced the expression of Bcl-2 and pCryAB and downregulated the expression of Bax, Cyt- c, Caspase-3, and Caspase-9 expression. Additionally, rosamultin might activate PI3K/Akt signal pathways and CryAB relative factors. Therefore, we suggest that rosamultin could have the potential for treating H2 O2 -induced oxidative stress injury through its antioxidant and antiapoptosis effect.